Relationship Between 3-Month Injection Contraception and Breast Milk Production - Madona Lolangion; Tut Rayani Aksohini Wijayanti; Reny Retnaningsih (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2025)
Exclusive breastfeeding is a practice where infants are fed only breast milk, without additional food, drink, or water, for the first six months of life. This practice is crucial for the infant’s growth and development. One factor that may affect breast milk production is the use of contraceptives, particularly the 3-month injection. This study aims to determine the relationship between the use of 3-month injections and the adequacy of exclusive breast milk production in mothers of children aged 7 to 23 months. A cross-sectional study design was employed, utilizing both primary and secondary data. The sample consisted of 72 mothers with children aged 7–23 months, of whom some used 3-month contraceptive injections and others did not. The data collected from the participants included their contraceptive usage and breast milk production status. The results showed that 29 out of 36 mothers (80.6%) who used 3-month injections still produced adequate amounts of breast milk. A bivariate analysis revealed a statistically significant relationship between the use of 3-month injections and the adequacy of exclusive breast milk production, with a p-value of 0.039. This finding suggests that, while most mothers who use 3-month injections still have sufficient breast milk production, there is a clear relationship between the use of contraceptive injections and the adequacy of milk. It is important to note that while the majority of mothers on 3-month injections maintained adequate milk production, the choice of contraceptive method during breastfeeding should still be carefully considered. Health workers play a vital role in providing guidance to ensure the best choice of contraception for breastfeeding mothers to support both maternal and infant health.